Watercolors Awash in Crayoned Responses: Teaching Narrative in Arts-based Praxis - Cynthia M. Morawski (Language and Literacy: A Canadian Educational e-journal, 2011)
I work in literacy education, encouraging teacher candidates to experiment with the arts to make a novel come alive for adolescent readers. Part of my research agenda, which is intertwined with my teaching, seeks to make sense of the question: What are the effects of arts-based learning on the teacher candidates’ theoretical and classroom practices? To first consider the above research question from my own pedagogical perspective, I draw on my earlier recollections (Adler, 1958) of arts and classroom living using the methodology of narrative inquiry—the study of the ways humans experience the world via the construction and reconstruction of their own stories (Connelly & Clandinin, 1990). Informed by my teaching narrative, crafted in the backdrop of remembered times, I venture forth to address the effects of arts-based learning on the teacher candidates’ theoretical and classroom practices. A more informed construction of our recurring narratives, rekindled by the illumination of early recollections, will play an integral role.